The Teachers’ Competencies to Develop Assessment for High School Students in Merauke - Desy Kumala Sari; Pri Ariadi Cahya Dinata; Rezky Uspayanti (AL-ISHLAH: Jurnal Pendidikan, 2022)
Competency in arranging and analyzing questions is essential for a teacher. This research was conducted to mapping the percentage and criteria of high school teachers' competency in Merauke District in preparing and analyzing the items question. The research included quantitative research by survey method. The data were collected using questionnaires with Likert scale. The obtained data were then analyzed using the Ideal Standard Deviation. The analyzed results showed the percentage of competencies of high school teachers in Merauke District in preparing and analyzing the question items is 74.66% which are in the "good" category, and the criteria for the quality of high school teachers' competencies in Merauke District in preparing and analyzing the question items are on the "good" criteria with an average score of 93.33. The results of the analysis based on aspects, the average teacher competency score in arranging the question item is 55.11 which is in the category of "good" while the competence of teachers in analyzing the question item is 36.86 which is in the category of "sufficient". Based on this, it is necessary to follow up to improve the competence of high school teachers in Merauke district in analyzing items question.